Elegant Economy in Elizabeth Gaskells Cranford: A Socialist Feminist Study (Global Journal of Human-Social Science, 2021)
Elizabeth Gaskell (1810-1865) was a Victorian writer who had to undergo various kinds of condescension for her writings. After bearing the stigma of being conformist, conventional, and meek as ascribed to her by the contemporary feminist critics, Gaskell's writings are being revisited with a new feminist perspective in recent years. The present paper is also a humble attempt to rediscover the feminist dimension of her writings by exploring one of her novels, Cranford (1853), through a socialist feminist lens. Cranford presents such a social structure that is devoid of a Class system and constructed by women in a matrilineal society as against the capitalist patriarchal society of Drumble. This Matriarchal socialist social structure is based on the values of cooperation, humanity, and motherly care characteristic to the differently developed gendered subjectivity of women. The social change through the agency of woman foreshadows Gaskell's far-sighted feminist views of the 1970s.
Keywords: elizabeth gaskell; cranford; victorian feminism; socialist feminism